Glycemic control according to glomerular filtration rate in patients with type 2 diabetes and overt nephropathy: A prospective observational study. Issue 1 (April 2015) - Joly, Dominique; Choukroun, Gabriel; Combe, Christian; Dussol, Bertrand; Fauvel, Jean-Pierre; Halimi, Jean-Michel; Quéré, Stéphane; Fiquet, Béatrice
Abstract Background and Objective Type 2 diabetes (T2D) and chronic kidney disease (CKD) are closely linked. This study aimed to describe and analyze the relations between renal function and glycemic control in T2D patients with overt nephropathy. Patients and methods Data were collected from a French observational prospective multicenter study. Patients included were adults with T2D, clinical proteinuria and an estimated glomerular filtration rate (eGFR) over 15 mL/min/1.73 m2. Baseline data and glycemic control after a one-year follow-up are presented here. Results Data from 986 adult patients were analyzed. Mean age was 70 years. Mean eGFR was 42 mL/min/1.73 m2, 66% of patients had proteinuria above 1 g/day. HbA1c was higher in patients with lower eGFR in a model adjusted to age, gender, body mass index, hemoglobin level and erythropoietin use. Statistical significance was lost when stepwise multivariate analysis took into account the type of pharmacological treatment used to treat hyperglycemia.The type of antidiabetic agents differed across eGFR strata. Below 60 mL/min/1.73 m2, the use of metformin declined while the use of insulin increased.After one year of follow up, 35% of patients had persistently poor or worsened glycemic control (HbA1c > 8%). The only covariate independently associated with this characteristic was the duration of insulin therapy. Conclusion In patients with T2D and overt nephropathy, the observed correlation of low eGFR with high HbA1c was not predicted by eGFR. Our data rather underscore a different use of antidiabetic treatments in patients with advanced renal dysfunction, and the difficulty to improve glycemic control in patients with long standing insulin therapy.